CONSTRUCTIVE ETHICS OF JUDGES IN INDONESIA; PROBLEMS AND STRATEGIC STRENGTHENING - Achmad Musyahid Idrus; Hisbullah Hisbullah; Sofyan Sofyan; Mulham Jaki Asti (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2022)
The existence of judges has been positioned as a fundamental and influential instrument for law enforcement in Indonesia. The role of judges in examining, adjudicating and even deciding cases actually relies on ethics and morality which have been fully outlined by the Law and other derivative regulations. This study aims to unravel the ethical ideals of judges from a juridical perspective, the reality of ethical problems of judges and strategies to strengthen judges in Indonesia. This type of research uses library research or library research through a review of relevant library materials. The results of the study show that the scope of judge ethics includes personality ethics, ethics in carrying out their duties, ethics for colleagues or fellow judges and ethics towards society or seekers of justice which as a whole are intended as a means of progress and personality formation, as a means of social control, and as a guarantee increase in the morality of judges. Despite the fact, the ethics and morality of judges are faced with problems stemming from the weaknesses in the personality of judges internally and the tension and ineffectiveness of the supervisory system externally. Therefore, the realization of a strong oversight policy by involving the Supreme Court as internal oversight and the Judicial Commission as external oversight is a strategic answer to overcoming the decline in the integrity and morality of judges, and is supported by constructive efforts such as strengthening the essential performance of the Honorary Panel of Judges in examining and deciding alleged violations of the code of ethics, stimulated the performance of the liaison team and judge supervisory assistants, strengthened strict sanctions in line with reward and punishment policies and built responsive legal values and culture.